EFFECTS OF CROSSWIND ON THE DRAG OF MEDIUM SPEED TRAINS - David Prayoga Paramaputera; Sheila Tobing; Matza Gusto Andika (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
Aerodynamic research on medium-speed trains is trying to map the flow of fluid around trains. The train model testing is conducted to study Cd values experimentally using a closed-loop wind tunnel at the Balai Besar Teknologi Aerodinamika, Aeroelastika, dan Aeroakustika. In addition to the experimental method, the computational method can be used to validate the experimental results, map the fluid flow around the train model, and calculate Cd values. The computational results of Cd obtained using ANSYS are compared against Cd values from wind tunnel tests. Further analysis using the ANSYS program with variations in the yaw angle can predict crosswind effects on the train model. It is found that vortices are formed around the train body, and modifying the head shape and adding fairing increases Cd values.